2015
DOI: 10.1089/ars.2014.6108
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase–Hepatocyte–Stellate Cell Cross Talk Promotes Hepatocyte Injury and Fibrosis in Experimental Nonalcoholic Steatohepatitis

Abstract: Cumulatively, these findings demonstrate important cross talk between inflammatory myeloid cells, hepatocytes, and HSCs via MPO and establish MPO as part of a proapoptotic and profibrotic pathway of progression in NASH, as well as a potential therapeutic target to ameliorate this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 59 publications
4
73
0
Order By: Relevance
“…Activated hepatic stellate cells (myofibroblasts) are a major source of extracellular matrix production leading to progressive liver fibrosis (Fig. ) . There is a paucity of data on the role of neutrophils in bile duct injury in BA that warrants further research based on the findings that elastase and NETs correlated with rising bilirubin post‐HPE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated hepatic stellate cells (myofibroblasts) are a major source of extracellular matrix production leading to progressive liver fibrosis (Fig. ) . There is a paucity of data on the role of neutrophils in bile duct injury in BA that warrants further research based on the findings that elastase and NETs correlated with rising bilirubin post‐HPE.…”
Section: Discussionmentioning
confidence: 99%
“…3). (41,42) There is a paucity of data on the role of neutrophils in bile duct injury in BA that warrants further research based on the findings that elastase and NETs correlated with rising bilirubin post-HPE. The small number of patients with BA analyzed in this study prohibits us from making any broad conclusions regarding the use of IL-8 as a biomarker of outcome in BA, and future studies should be appropriately powered in order to determine the accuracy of IL-8 as a biomarker of severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Activated neutrophil‐mediated oxidative stress results in a reduced capacity for nucleotide excision repair, which could further reduce DNA damage recognition and potentiate liver cancer development . Genetic or pharmacological elimination of MPO, NE, or proteinase 3 expression or activity diminishes HFD‐induced pathological changes in NASH …”
Section: Innate Immune Cellular Players In Nashmentioning
confidence: 99%
“…(23) Genetic or pharmacological elimination of MPO, NE, or proteinase 3 expression or activity diminishes HFDinduced pathological changes in NASH. (23,33,34)…”
Section: Neutrophilsmentioning
confidence: 99%
“…Work by both Pulli et al 5 and Novo et al 6 have shown that neutrophil-derived oxidative species can facilitate the recruitment of hepatic stellate cells, thereby activating profibrotic pathways. Neutrophils themselves have been shown to be involved in fibrosis through the secretion of interleukin (IL)-6 needed for the differentiation of T helper 17 cells,7 as well as being a direct source of IL-17 8.…”
mentioning
confidence: 99%